TOWARDS A SHARED MEDITERRANEAN WATER INFORMATION SYSTEM - EL KHARRAZ, Jauad (European Scientific Journal, ESJ, 2014)
This project aims at implementing ―data, information and statistics on water, based on internationally agreed definitions and methods, structured within information systems, for analysis and decision making‖ as requested by the UfM Ministerial conference on Water (Jordan, December 2008). Information has been identified as a weak point for many Mediterranean countries regarding their national strategy, especially insufficient knowledge about water abstractions or economic data, or regarding transboundary water resources management. In order to address these issues and to be sure that the deliveries of the project will be used in a sustainable manner, the scope of the project includes all data required for Integrated Water Resources Management Planning and Water Regulation at a river basin or aquifer level or at national and regional level. The objective of project first step for the next 3 years is to create Shared National Water Data Management Systems in 4 pilot countries, to prepare tools for deploying such systems in all the Mediterranean Countries and to set in place an automated reporting mechanism to some regional organizations on a voluntary basis. The extension to other countries or to other topics will be considered in a second step or another project that could be defined on the basis of the results of the current project. Beyond the creation of national systems which will benefit mainly to the pilot countries, all the Mediterranean countries will have the opportunity to take part in regional activities and will benefit from the results of the project first step.